2017
DOI: 10.1002/ceat.201600343
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Operating Parameters on Biomass Conversion under Sub‐ and Supercritical Water Conditions

Abstract: The influence of reaction pressure, reaction time, reaction temperature, and biomass‐to‐water mass ratio R on the conversion of miscanthus biomass to biofuels under sub‐ and supercritical water (SCW) conditions was investigated. The highest total conversion was obtained under SCW conditions and the heating value increased under subcritical and SCW conditions. The findings herein show that near‐supercritical and supercritical water at 400 °C and high pressure can be an effective reaction medium for converting b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Methanol ( T C = 239 °C, Pc = 8.1 MPa) with mild critical condition has similar physical properties with water in supercritical region. Both supercritical methanol ( SC MeOH) and SC H 2 O have a static dielectric constant as low as 2, possessing good solubility to organics . The synthesis of biodiesel in a high-pressure view cell revealed that the mixture of vegetable oil and dense SC MeOH could form a single phase .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methanol ( T C = 239 °C, Pc = 8.1 MPa) with mild critical condition has similar physical properties with water in supercritical region. Both supercritical methanol ( SC MeOH) and SC H 2 O have a static dielectric constant as low as 2, possessing good solubility to organics . The synthesis of biodiesel in a high-pressure view cell revealed that the mixture of vegetable oil and dense SC MeOH could form a single phase .…”
Section: Introductionmentioning
confidence: 99%
“…20 With the intensification of the forgoing degradation at moderate temperatures, the secondary condensation could be terminated promptly at a shortened reaction time. By the fact that the cracking of alkyl substitutes of aromatics and the cracking of waxes follow exactly the same approach, an effective pour point reduction is supposed to be 21 The synthesis of biodiesel in a high-pressure view cell revealed that the mixture of vegetable oil and dense SC MeOH could form a single phase. 22 The reaction kinetics analysis of the upgrading of heavy oil in SC H 2 O suggested that, at a high SC H 2 O density and a high SC H 2 O to oil ratio, the reaction system might transit to a pseudo single-phase.…”
Section: Introductionmentioning
confidence: 99%
“…Several processes, such as thermal‐chemical process and biochemical process, can be applied to convert lignin into fuel or chemicals. Hydrothermal liquefaction (HTL), a kind of thermal‐chemical conversion technique, uses liquid subcritical or supercritical water as reaction medium for the conversion of biomass and waste streams . In that process, with high‐temperature and high‐pressure water, organic macromolecules are depolymerized into low‐molecular‐weight compounds and monomers, meanwhile some resultant products are still obtained in different phases, namely, gas phase, solid phase, and liquid phase.…”
Section: Introductionmentioning
confidence: 99%